survey of myocardial perfusion scan findings using Tc99 m in patients referred to Birjand nuclear medicine in 2012 - Mahmud Reza Tavakolli (Journal of Birjand University of Medical Sciences, 2013)
Background and Aim: As more people are at risk of cardiovascular diseases the demand for screening them is increasing. Myocardial perfusion imaging (MPI),due to not being aggressive, is used for the detection of coronary diseases and ,moreover, for the finding of the extent, severity, and location of ischemia. In the present study,myocardial perfusion scans were assessed. Materials and Methods: The present descriptive-analytical study was done on 350 patients who had been referred to Birjand nuclear medicine center during the second half of 2011. The necessary data was collected by the means of a questionnaire addressing demographic information, personal and family history of diseases, cardiac abnormalities, blood pressure, diabetes, and the type of heart lesions. The obtained data,then, was fed into SPSS software (V:19) and statistical analysis was performed. Results: Mean age of the cases was 57.1±11.8 years. Women consisted 58.6% of them,86.6% were citizens,and . 34% had a familial history of. Heart lesions were diagnosed in 40% out of which 85% had ischemic problems and 15% suffered myocardial infarction.Relative frequency of in men was higher compared to women (P<0.001).It was found that there was a significant relationship between and diabetes (P<0.05).But, no significant relationship was found between and their types with age, habitation, and familial ties. Conclusion: The present study showed that myocardial perfusion imaging, as a non-aggressive method in diagnosing heart lesions, can be helpful.